CREDIT RISK MANAGEMENT AND NON-PERFORMING LOAN DYNAMICS IN HOME OWNERSHIP LENDING: EVIDENCE FROM AN INDONESIAN STATE-OWNED BANK - Putri Handayani (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study aims to analyze the application of credit risk management in PT Bank Tabungan Negara (Persero) Tbk's Home Ownership Loan (KPR) products during the 2022–2024 period. Credit risk is a major risk in banking that has the potential to affect asset quality and stability of banks' financial performance, especially in banks with a focus on housing financing such as BTN. The research method used is a qualitative and quantitative descriptive approach by utilizing secondary data in the form of financial statements, risk management reports, as well as official publications of BTN and relevant scientific journals. The analysis focused on the development of Non-Performing Loan (NPL) ratios, the application of prudential principles, and mortgage credit risk mitigation strategies. The results show that the NPL ratio of BTN MORTGAGES during the 2022–2024 period has experienced an increasing trend, but is still at a relatively controlled level. BTN consistently implements credit risk management through 5C-based feasibility analysis and continuous credit supervision. This study concludes that the effectiveness of credit risk management plays an important role in maintaining the quality of mortgage credit and the sustainability of BTN's performance.